Associations between the thyroid panel and serum protein concentrations across pregnancy - Barbara Lisowska-Myjak; Agnieszka Strawa; Hanna Zborowska; Artur Jakimiuk; Ewa Skarżyńska (Scientific Reports, 2021)
Abstract Establishing any characteristic associations between the serum parameters of thyroid function and serum proteins in pregnancy may aid in elucidating the role of the thyroid gland in the regulation of pregnancy-specific metabolic processes and in selecting candidate biomarkers for use in their clinical assessment. Concentrations of thyroid stimulating hormone (TSH), free tri-iodothyronine (fT3) and free thyroxine (fT4), six electrophoretically separated protein fractions (albumin, alpha-1-, alpha2-, beta-1-, beta-2- and gamma-globulins), representative proteins—albumin (ALB), transferrin (TRF), alpha-2-macroglobulin (AMG) and ceruloplasmin (CER) were measured in 136 serum samples from 65 women in their consecutive trimesters of pregnancy. The concentrations of TSH, fT4 and fT3 were significantly correlated (p < 0.05) with the concentrations of the albumin, alpha-2- and beta-1 globulin fractions. Significant correlations (p < 0.05) which were positive between fT4 and ALB and negative between fT4 and TRF were established throughout pregnancy. Significant negative correlations (p < 0.05) were demonstrated for fT3 with alpha-2-globulin, AMG and CER. Changes in the serum concentrations of thyroid hormones seen between the trimesters were found to correlate with the concentrations of high-abundance serum proteins. Opposite directions of correlations between fT4 and ALB and fT4 and TRF observed throughout pregnancy may indicate the shared biological role of these parameters in maintaining maternal homeostasis and they suggest their potential use in the clinic as a simple biomarker panel. A negative correlation of fT3 with CER in the second trimester possibly reflects their involvement in the active regulation of metabolic processes.